2019
DOI: 10.1002/psp.2279
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of migration and household member arrangement among poor rural households in China: The case of North Jiangsu

Abstract: After decades of rural‐to‐urban migration, alleviating poverty among rural populations has become a priority of the central government of China. Migration is assumed to be a strategy for poor rural populations to cope with poverty. Nevertheless, extant research has paid little attention to migration determinants and household arrangements of poor rural populations in particular. Moreover, existing literature regarding migration in China from a household perspective is relatively scare. Therefore, based on a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 56 publications
2
10
0
Order By: Relevance
“…(2) There is a positive and significant correlation between indicators related to the increase in poverty (VPR and VPG) and that related to the increase in rural population (VRP). This type of relationship has been previously described in other studies carried out in depressed territories, where the population finally migrates to escape poverty [89][90][91][92][93]. (3) Demographic characteristics are correlated between them.…”
Section: Relationship Between the Territorial Changes Observedsupporting
confidence: 59%
“…(2) There is a positive and significant correlation between indicators related to the increase in poverty (VPR and VPG) and that related to the increase in rural population (VRP). This type of relationship has been previously described in other studies carried out in depressed territories, where the population finally migrates to escape poverty [89][90][91][92][93]. (3) Demographic characteristics are correlated between them.…”
Section: Relationship Between the Territorial Changes Observedsupporting
confidence: 59%
“…Constrained by high living costs in cities and difficulties accessing local public schools, migrant parents often send children back to the origin under the care of grandparents, or arrange to have one parent supervise the children's schooling in the hometown, while the other one continues to work outside to support the family financially (Unger and Siu, 2019). Grandparents also engage in household strategies in that they provide childcare and undertake domestic work to support their migrant children (Tang, 2020). Cultural traditions, including patricentric thinking and filial piety, have dominated familial decision-making and the functioning of household strategy (Lee, 2015;Qi, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, migrants with a higher educational attainment are more capable of integrating into and settling in the host city (Fan & Chen, 2012; Yang & Guo, 2018). Recent studies based on survey data collected in one or several cities have shown that an increasing number of migrants have an ambivalent identity, considering themselves as a part of the host society and that they are increasingly willing to settle permanently in the host city (Chen & Fan, 2018; Chen et al, 2020; Dang et al, 2019; Hao & Tang, 2018; Huang et al, 2018; Liu et al, 2016; Tang, 2019; Tang & Hao, 2019; Xie et al, 2017; Yang & Guo, 2018). However, despite a strong intention to settle in the host city, many migrants have few resources and are confronted with multiple constraints in the destination, which reduces their opportunity to integrate into the host society (Fan, 2011; Knight & Gunatilaka, 2010; Zhu, 2007; Zhu & Chen, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…They assumed that most migrant workers were satisfied with their socio‐economic status in the host city, as migrants' social identity remained rooted in sending communities, and their reference group for social comparison remained their relatives and friends in sending communities (Chan & Buckingham, 2008; Nielsen, Smyth, & Zhai, 2010; Zheng, Long, Fan, & Gu, 2009). More recent studies have shown that migrant workers were diversified in terms of social identity and settlement intention and that an increasing number of migrant workers had a local identity and were willing to settle permanently in the host city (Chen & Fan, 2018; Chen, Wang, Liu, & Liu, 2020; Dang, Chen, & Dong, 2019; Hao & Tang, 2018; Huang, Liu, Xue, Li, & Shi, 2018; Liu, Wang, & Chen, 2016; Tang, 2019; Tang & Hao, 2019; Xie, Wang, Chen, & Ritakallio, 2017; Yang & Guo, 2018). Some migrants, especially those who were born after 1980 (“new generation migrants”), tended to shift their reference group from sending communities to their peers in receiving communities over time, and they tended to suffer from a mismatch between rising aspirations for a better life and the realities of poor working and living conditions (Cheng, Wang, & Smyth, 2014; Huang et al, 2017; Jin, 2016; Knight & Gunatilaka, 2010).…”
Section: Introductionmentioning
confidence: 99%